2019
DOI: 10.3390/genes10050376
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Novel Reference Genes in Acute Lymphoblastic Leukemia for Droplet Digital PCR

Abstract: Droplet digital PCR is the most robust method for absolute nucleic acid quantification. However, RNA is a very versatile molecule and its abundance is tissue-dependent. RNA quantification is dependent on a reference control to estimate the abundance. Additionally, in cancer, many cellular processes are deregulated which consequently affects the gene expression profiles. In this work, we performed microarray data mining of different childhood cancers and healthy controls. We selected four genes that showed no g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Primers for ABCG1, ABCG2, and ABCB1genes (23) were designed according to the Table 1. GAPDH gene was used for the normalization of the results through RT-PCR with a forward primer (5' -3'): GAAGGTGAAGGTCGGAGTC and reverse primer (5' -3'): GAAGATGGTGATGGGATTTC (24,25). The specificity of primers had been checked with primer blast (26).…”
Section: Real-time Pcr (Rt-pcr)mentioning
confidence: 99%
“…Primers for ABCG1, ABCG2, and ABCB1genes (23) were designed according to the Table 1. GAPDH gene was used for the normalization of the results through RT-PCR with a forward primer (5' -3'): GAAGGTGAAGGTCGGAGTC and reverse primer (5' -3'): GAAGATGGTGATGGGATTTC (24,25). The specificity of primers had been checked with primer blast (26).…”
Section: Real-time Pcr (Rt-pcr)mentioning
confidence: 99%
“…Partitions are then subject to fluorescent probes, and each reaction chamber is examined for either the presence or absence of fluorescence. The frequency of positive amplifications is analyzed using the Poisson distribution to determine the template concentration [71]. The use of digital PCR (dPCR) was first published in 1999 in a paper by Vogelstein and Kinzler in which the feasibility of dPCR was demonstrated through the detection of a mutant RAS oncogene.…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%
“…Their use of dPCR differed from ddPCR in the method and degree of sample partitioning [72]. ddPCR has been commercially available since 2011 [73,74] and has been used to successfully detect MRD in leukemia samples and predict relapse [71,75]. ddPCR increases the sensitivity of detection to one blast cell in 10 6 cells compared to 10 5 cells in RQ-PCR.…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%
“…Systematic Review of 122 articles yielded 43 RGs used in haematological malignancies through (a) selection of genes by different analysis methods (S4 Table) and (b) usage of known RGs in qPCR (S1 Table). FPKM values of all these RGs when examined in 4 public databases showed varied expression among different types of haematological malignancies (S3 and S4 Figs) with maybe the exception of PGGT1B [22]. However, since other genes selected in the literature showed higher expression and correlated extreme variation, we could not depend on the assay and proceeded to select novel RGs with an unbiased approach.…”
Section: Systematic Review Of Commonly Used Rgs From Literaturementioning
confidence: 99%
“…This study, through a systematic review of literature in haematological malignancies concluded that mostly conventionally used "house-keeping" genes are still being deployed (S1 Table and S1 Fig) despite their varied expression based on cell type, developmental stage and experimental conditions [20] with rare exceptions [21,22]. None of the 43 genes thus identified could be used to relatively quantify BCL2 as molecular diagnostics since compared to the FPKM (Fragments Per Kilobase of transcript per Million mapped reads) value of the anti-apoptotic genes across 4 databases (S2 Fig), most of the RGs from the literature are not only higher, but also varied significantly (S3 and S4 Figs) with few exceptions.…”
Section: Introductionmentioning
confidence: 99%